Fluorescence in situ hybridisation detection of erbB2 amplification in breast cancer fine needle aspirates. Issue 2 (1st April 1999) - McManus, D T; Patterson, A H; Maxwell, P; Humphreys, M W; Anderson, N H
Abstract : AIM: To develop a method for the detection of amplification of the erbB2 oncogene in breast cancer fine needle aspirates using fluorescence in situ hybridisation (FISH) and to compare amplification with immunohistochemical detection of the erbB2 protein. METHODS: A digoxigenin labelled probe to the erbB2 gene was hybridised to 15 aspirates prepared from operative breast cancer specimens. A chromosome 17 centromere probe was also hybridised to the aspirates either separately or in combination with the erbB2 probe. The aspirates were scored for erbB2 amplification and chromosome 17 centromere number. Subsequently, paraffin wax embedded sections of the tumours were stained with the antibody CB11 and scored for the presence of membrane staining. RESULTS: Three of the 15 tumour aspirates showed high level amplification of erbB2 detected by FISH. These three tumours also showed chromosome 17 polysomy and diffuse membrane staining by immunohistochemistry. CONCLUSIONS: FISH can be used to detect erbB2 amplification in fine needle aspirates and results correlate with conventional immunohistochemical staining. Difficulties were encountered in the visualisation of the signals in non-amplified cases without the use of specialised digital imaging.